2015
DOI: 10.3389/fncom.2014.00171
|View full text |Cite|
|
Sign up to set email alerts
|

Correlated activity supports efficient cortical processing

Abstract: Visual recognition is a computational challenge that is thought to occur via efficient coding. An important concept is sparseness, a measure of coding efficiency. The prevailing view is that sparseness supports efficiency by minimizing redundancy and correlations in spiking populations. Yet, we recently reported that “choristers”, neurons that behave more similarly (have correlated stimulus preferences and spontaneous coincident spiking), carry more generalizable object information than uncorrelated neurons (“… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 113 publications
(191 reference statements)
0
14
0
Order By: Relevance
“…In addition, noise correlation (R sc ) is higher for choristers than soloists in IT cortex [18]. Anatomical differences were also observed since the cortical laminar distribution for these types of units is distinct [18]. In mouse V1, population coupling varies between the narrow-spiking and regular-spiking neurons; however, this difference was reported to be smaller than the class-variability [27].…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…In addition, noise correlation (R sc ) is higher for choristers than soloists in IT cortex [18]. Anatomical differences were also observed since the cortical laminar distribution for these types of units is distinct [18]. In mouse V1, population coupling varies between the narrow-spiking and regular-spiking neurons; however, this difference was reported to be smaller than the class-variability [27].…”
Section: Introductionmentioning
confidence: 91%
“…It has been suggested that soloists are distinct from choristers in many aspects such as the synaptic connectivity [27] and the laminar distribution [18]. We examined the relationship between the waveform type, the firing rate and the correlation-strength of the cells' firing with the population activity.…”
Section: Firing Rate Spike-type and Categorization Of Soloists And Cmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, core cells differentially combine with cells from a larger pool of inconsistently responding neurons to a given stimulus presentation. 'Core' cells of an assembly have only recently been described in the literature, but only in the context of cells most representative of, or having the highest correlation to, a particular responding cluster (Carrillo-Reid et al, 2015;Hung et al, 2015;Lin et al, 2014). To the best of our knowledge, this study provides the first description of a spatially localised population P ag e 138 of core cells in tectal assemblies that respond consistently and are more selective for their preferred stimulus features.…”
Section: Assembly Coresmentioning
confidence: 99%
“…Using eight-pin, multi-site electrodes, two recent studies have been able to describe the presence of 'core' cells in the macaque inferior temporal cortex (Hung et al, 2015;Lin et al, 2014). More recently, the presence of core cells in the mouse visual cortex have also been described from calcium dye recordings (Carrillo-Reid et al, 2015).…”
Section: Assembly Coresmentioning
confidence: 99%